2012
DOI: 10.1080/10454438.2012.679164
|View full text |Cite
|
Sign up to set email alerts
|

Soy Protein Concentrate as an Alternative Ingredient in Florida Pompano (Trachinotus carolinus) Diets

Abstract: Current research is intended to develop cost-effective, plant-based diets for intensive production of Florida pompano ( Trachinotus carolinus). Three growth trials were conducted with juvenile pompano over a 106-to 115-day period. The trials evaluated the systematic substitution on an equal protein basis of (1) menhaden fish meal, FM with soy protein concentrate (SPC), and (2) solvent extracted soybean meal (SBM) with SPC. This confirmed the reduction of FM and evaluated the possible nutrient restrictions of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 20 publications
2
14
1
Order By: Relevance
“…The results of Trial I showed that the utilization of meat and bone meal in diets with soybean meal at 50% was effective at reducing the level of fish meal from 15 to 5% without significant effects on growth performance and survival of Florida pompano. However, the overall performance of the fish was low relative to that observed in other studies (Lazo et al ; Riche ; Quintero et al ). Although different studies preclude direct comparisons, these observations indicated potential limitations in the diets of Trial I.…”
Section: Discussioncontrasting
confidence: 67%
“…The results of Trial I showed that the utilization of meat and bone meal in diets with soybean meal at 50% was effective at reducing the level of fish meal from 15 to 5% without significant effects on growth performance and survival of Florida pompano. However, the overall performance of the fish was low relative to that observed in other studies (Lazo et al ; Riche ; Quintero et al ). Although different studies preclude direct comparisons, these observations indicated potential limitations in the diets of Trial I.…”
Section: Discussioncontrasting
confidence: 67%
“…In this study, the reduced growth performance of Florida pompano when 15% inclusion level of FM further replaced with soy protein, confirmed the observations of the previous study as demonstrated by Quintero et al (). In trial 1, a gradual reduction in FW is consistent with decreasing number of TGC and higher FCR.…”
Section: Discussionsupporting
confidence: 92%
“…We have verified that 15% FM protein to maintain 40% crude protein (CP) level as the reference in the development of practical diet for Florida pompano may be considered as the minimum inclusion level that still supports optimum growth of this fish (Quintero et al, ; Rossi & Davis, ). Continued reduction in FM levels will likely reduce the growth performance of this species (Cook, Zhou, Rhodes, & Davis, ).…”
Section: Introductionmentioning
confidence: 87%
“…In this study, using a combination of CPC and SPC to replace fishmeal provided a complimentary advantage. This helped maintain a balanced amino acid profile in practical shrimp diets, enhanced palatability and simultaneously improved digestibility (Hu et al, ; Quintero, Davis, & Rhodes, ). Similarly, Kissinger, García‐Ortega, and Trushenski () reported that a combination of algal and soy protein can account for more than half of the total protein in a low fishmeal diet.…”
Section: Discussionmentioning
confidence: 99%